The long journey towards standards for engineering biosystems: Are the Molecular Biology and the Biotech communities ready to standardise? - Beal, Jacob (EMBO Rep, 2020)
Synthetic biology needs to adopt sound scientific and industry‐like standards in order to achieve its ambitious goals of efficient and accurate engineering of biological systems.[Image: see text]